In action - "Brown, Justin" (Hawthorn; Mimosa/McGraw-Hill, 2007)
Mike organises a Backyard Olympics, goes into space, creates a video game for serious adults and tries some extreme sports
Donated by "Book Planet", Dated 18-4-2025.
Keywords: Humorous fiction